A Study on the Method of Detecting the Ghost-Key Phenomenon of Rubber Contact Switch Type Remote Controller for the Smart-TV - Kwon, Sung-Yeol; Lee, Hyun-Chang (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, ghost-key phenomenon detection method was proposed for rubber contact switch type remote controller of smart-TV.Methods/Statistical analysis: The principle of ghost-key phenomenon is analyzed when the switches are pressed simultaneously. The requirements of pull-up resistor ratio are obtained by case study with a circuit modeling. The proposed method is an optimized design that the switch has the greatest voltage difference between the normal state and the ghost-key state.Findings: In order to verify the proposed method, a remote controller with a rubber contact switch and a microcontroller were set up and tested based on theoretical values. The performance of proposed method was verified that the voltage is apparently distinguishes between normal state and ghost-key state. As a result, analog-to-digital conversion of the microcontroller can be used to detect and remove the ghost-key.Improvements/Applications: The proposed method can overcome limitations of other equipment with rubber contact switch. Therefore, the application range of rubber contact switch is expected to be expanded.Â